2012
DOI: 10.1007/s11250-011-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

A description of local pig feeding systems in village smallholder farms of Western Kenya

Abstract: We used face-to-face interviews to gather data on pig feeding practices in rural Busia District, Kenya. We visited 164 pig farms three times in the course of the study period. The pigs were weighed in kilograms during the visits. Feeds offered to pigs were described during the interviews. The most frequently fed feedstuffs were; ground maize or "ugali" (88%), kitchen leftovers (83%) and dried fish locally called "omena" (78%). Farmers provided pigs with water separately from the feeds. Sweet potatoes, "ugali" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 8 publications
4
46
1
Order By: Relevance
“…Thirty-five locally available potential feedstuffs for pigs were identified by Mutua et al (2012) and Kagira et al (2010). Based on the scientific literature and interviews with local agriculture extension officers, these feedstuffs were ranked according to their appropriateness for widespread use for pigs considering their use as human food rather than feed, relative cost, palatability, zoonotic disease risk, anti-nutritional factors and toxins, and likelihood of widespread accessibility and adoption by pig keepers.…”
Section: Materials and Methods Selection Of Feedstuffs Sampling And mentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-five locally available potential feedstuffs for pigs were identified by Mutua et al (2012) and Kagira et al (2010). Based on the scientific literature and interviews with local agriculture extension officers, these feedstuffs were ranked according to their appropriateness for widespread use for pigs considering their use as human food rather than feed, relative cost, palatability, zoonotic disease risk, anti-nutritional factors and toxins, and likelihood of widespread accessibility and adoption by pig keepers.…”
Section: Materials and Methods Selection Of Feedstuffs Sampling And mentioning
confidence: 99%
“…Pigs in western Kenya are generally fed inadequate diets because of high costs and seasonal shortages of appropriate feedstuffs (Kagira et al 2010;Mutua et al 2012). As a result, mean average daily gain of growing pigs on smallholder farms is low at 130920 g d…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, smallholder farmers in Lao PDR commonly provided their pigs with feed twice a day, but underfeeding was often observed (Phengsavanh et al 2010). In a recent description of local feeding systems on smallholder farms in Kenya, pigs were fed once or twice a day, and water was provided separately with the food (Mutua et al 2012), which is comparable to Mbeya Region. Improved local feeds have been suggested to increase production output at the smallholder level (Lekule & Kyvsgaard 2003).…”
Section: Figurementioning
confidence: 99%
“…In this system of pig rearing cost involved for feed was low. Several authors (Mutua et al, 2012;Carter et al, 2013) reported that it becomes popular and plays an important role in the livelihood of many families in rural villages of Western Kenya by practicing this type of feeding. In this report, pigs of the control groups showed better performances in respect of reproductive and productive performances indicating addition of easily digestible energy rich concentrate helps to increase the productivity.…”
Section: Effect Of Zn Supplementation On Growth Performancesmentioning
confidence: 99%